Testing the EKC hypothesis for the top six hydropower energy-consuming countries: Evidence from Fourier Bootstrap ARDL procedure. (10th August 2020) - Pata, Ugur Korkut; Aydin, Mucahit
Abstract: Environmental degradation is an important threat to sustainable development. Economic growth and fossil fuel-based energy consumption are main factors causing environmental pollution. The use of renewable energy as an alternative for fossil fuels can help to reduce environmental pollution, and thus, sustainable development can be achieved. From this point of view, hydropower is the most widely used renewable energy source in several countries. However, the effects of hydropower energy on the environment are controversial. To add a new dimension to the discussion, this study investigates the relationship between hydropower energy consumption, ecological footprint and economic growth for the top six hydropower-consuming countries within the framework of the environmental Kuznets curve (EKC) hypothesis. The study employs newly developed cointegration and causality tests with smooth structural changes over the period 1965–2016. The findings of the Fourier bootstrap ARDL procedure demonstrate that no cointegration exist between the variables. Therefore, the EKC hypothesis is not valid for Brazil, China, Canada, India, Norway and the US. Furthermore, the findings of the Fourier Toda-Yamamoto causality test suggest unidirectional causality running from hydropower energy consumption to economic growth in Brazil, and bidirectional causality between these variables in China. In the case of the top six hydropower-consuming countries, no evidence was found for a causal relationship between hydropower energy and ecological footprint. Overall, these results are important for policy makers. Hydropower energy plays a crucial role in China and Brazil's economic growth policies. On the other hand, hydropower energy consumption and economic growth do not have a role in mitigating the ecological footprint in six countries. For this reason, different types of renewable energy consumption should be taken into consideration by countries for the solution of environmental problems. Graphical abstract: Image 1 Highlights: Fourier unit root, causality and cointegration tests are employed. The EKC does not hold in the top six hydropower energy consuming countries. No causal nexus between hydropower energy consumption and ecological footprint. Hydropower energy is not used effectively enough to reduce ecological footprint. Other renewable energy sources need to be promoted for sustainable development.